Alternative Complement Pathway Is Activated and Associated with Galactose-Deficient IgA1 Antibody in IgA Nephropathy Patients - Chiu, Yen-Ling; Lin, Wei-Chou; Shu, Kai-Hsiang; Fang, Yi-Wen; Chang, Fan-Chi; Chou, Yu-Hsiang; Wu, Ching-Fang; Chiang, Wen-Chih; Lin, Shuei-Liong; Chen, Yung-Ming; Wu, Ming-Shiou (Frontiers in Immunology, 2021)
Background Galactose-deficient IgA1 (Gd-IgA1) and alternative complement pathway activation are considered to be involved in the pathogenesis of IgA nephropathy (IgAN). Nevertheless, the relationships between alternative pathway activation and disease activity or Gd-IgA1 level remains unclear. Methods Ninety-eight biopsy-diagnosed IgAN, twenty-five primary focal segmental sclerosis (FSGS) patients and forty-two healthy individuals were recruited in this study. Among them, fifty IgAN patients received immunosuppression. Follow-up blood samples at 1 and 3~6 months after immunosuppression were collected. Plasma levels of complement C5a, factor Ba and Gd-IgA1 were measured and analyzed. Immunostaining for complement was performed in twenty-five IgAN and FSGS patients. Results At baseline, IgAN patients had higher levels of plasma C5a, factor Ba and Gd-IgA1 than control subjects. Gd-IgA1 levels positively correlated with plasma C5a and factor Ba. In addition, levels of factor Ba and Gd-IgA1 were positively associated with proteinuria and negatively associated with renal function. Immunostaining revealed positive staining for factor Bb and C3c in glomeruli in IgAN patients, but not in FSGS patients. At baseline, patients receiving immunosuppression had more severe proteinuria and higher factor Ba. After 6 months, eGFR declined and proteinuria persisted in patients without immunosuppression. In contrast, patients who received immunosuppression exhibited decreased plasma levels of C5a, factor Ba, and Gd-IgA1 as early as 1 month after treatment. Proteinuria decreased and renal function also remained stable 6 months after immunosuppression. Conclusions Our results indicate a close relationship between alternative complement pathway activation, Gd-IgA1 concentration and clinical severity of IgAN. Level of complement factor B may be a potential marker for disease activity and therapeutic target in IgAN patients.